Ujaran Kebencian (Hate Speech) Pada Public Figure Dalam Kolom Komentar Di Media Sosial - Rizkiyah, Ai; Mayasari, Mayasari; Budhiharti, Tri Widya (Peneliti.net, 2024)
Social media applications, especially online, can make it easier for someone to find the latest information. So, the use of the Instagram application has become a habit that almost every day is not forgotten by all of us. Since the emergence of social media that is easily accessible to all circles, it is undeniable that new social problems have begun to emerge, such as hate speech that often occurs, one of which is in the comments column. This study aims to determine the hate speech or hate speech in Lesti Kejora's child in the comments column of the @lestikejora Instagram account. Using a qualitative research method with a case study approach supported by Anne Waber's hate speech theory. The subjects in this study consisted of five informants who were selected based on certain criteria. The data collection techniques used are observation, interview, and documentation. The results showed that there are forms of expression of hate speech which are divided into 4, namely insults, provocations, unpleasant actions, and defamation. Then there is a factor of hate speech due to users who are provoked by comments written by others who make themselves feel that many netizens are of the same mind as them. Then, there is an awareness recognized by the perpetrators of the impact of writing hate speech in the comments column that can have a negative impact, namely interference with the victim's mental health.